1995
DOI: 10.1002/ccd.1810340403
|View full text |Cite
|
Sign up to set email alerts
|

Systemic anaphylactoid reactions to lodinated contrast media during cardiac catheterization procedures: Guidelines for prevention, diagnosis, and treatment

Abstract: This report represents the first guidelines for prevention, diagnosis, and treatment of anaphylactoid reactions to contrast media occurring specifically during cardiac catheterization. The incidence of contrast media complications in the catheterization laboratory is 0.23% with 1 death per 55,000. Anaphylactoid reactions are nonimmune mediated, but histamine release and other mediators produce a clinical presentation indistinguishable from anaphylaxis. In patients with known previous reactions, pretreatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…1) Adverse reactions related to nonionic contrast media are estimated at 5-10%. 2,3) These incidence rates are consistent with available data on adverse reactions for non-invasive radiologic procedures. 4) Renal injury from contrast media is widely established and there are a few proposed risk models to predict the risk of renal injury.…”
Section: Discussionsupporting
confidence: 84%
“…1) Adverse reactions related to nonionic contrast media are estimated at 5-10%. 2,3) These incidence rates are consistent with available data on adverse reactions for non-invasive radiologic procedures. 4) Renal injury from contrast media is widely established and there are a few proposed risk models to predict the risk of renal injury.…”
Section: Discussionsupporting
confidence: 84%
“…As stated at the outset, there is scanty evidence relating specifically to management of iron infusions: the recommendations made below are drawn from other contexts in which IV drugs are given. 17,[27][28][29][30][31] The selection of individual drugs for treatment of HSRs and their doses and routes of administration vary and can be modified according to local practice.…”
Section: How Should Hypersensitivity Reactions To Intravenous Iron Bementioning
confidence: 99%
“…30 Their therapeutic benefit is unclear, and indeed, by sometimes potentiating tachycardia, hypotension and somnolence, H1 antagonists can make an HSR appear more hemodynamically significant.…”
Section: How Should Hypersensitivity Reactions To Intravenous Iron Bementioning
confidence: 99%
“…Goss et al in 1995 reported incidence of contrast related severe anaphylactic reaction to be 0.23% in Cathlab during cardiac catheterisation. 19 Contrast induced nephropathy (CIN) is an iatrogenic renal injury that follows intravascular administration of radio-opaque contrast media. Expectedly more and more patients are at risk of developing CIN with advancement of radioimaging diagnostic and therapeutic modalities and its ever-increasing use.…”
Section: Discussionmentioning
confidence: 99%